Calibration of bi-planar radiography with a minimal-size calibration object - Daniel C. Moura (2008)
Methods based on bi-planar radiography enable performing 3D reconstructions of bone structures (e.g. spine)with much less radiation than CT. These methods require a calibration procedure that must be executed forevery examination to capture the geometrical parameters of the imaging system. In most of the publishedwork, calibration is performed using non-standard equipments of large dimensions that enclose the patient andintroduce undesirable objects into radiographs. In this paper we propose a method for geometrical calibrationof bi-planar radiography that aims at minimising the impact of calibration objects on the content ofradiographs, while requiring minimal adaptations to standard x-ray imaging systems.